UNDERSTANDING THE EFFECTS OF BROKEN HOMES ON STUDENTS: FAMILY STRUCTURE, PARENTING PATTERNS, AND EDUCATIONAL ACHIEVEMENT - Prisca Diantra Sampe (International Journal of Teaching and Learning, 2026)
This study aims to examine the effects of broken-home conditions on students’ socio-emotional development and educational achievement through a literature review approach. Family instability, including parental divorce, prolonged conflict, emotional neglect, and dysfunctional parenting, has become an increasingly significant issue in contemporary education because it influences students’ psychological well-being, social adaptation, and academic performance. This research employed a qualitative library research method by analyzing recent scholarly publications indexed in reputable databases such as Scopus, ScienceDirect, SpringerLink, and Google Scholar. The selected literature primarily focused on studies published within the last 2 years that examined family structure, parenting patterns, social support, socio-emotional development, and educational achievement among students from broken-home families. The findings indicate that broken-home conditions negatively affect students through increased emotional distress, anxiety, low self-esteem, social withdrawal, reduced learning motivation, and declining academic engagement. Parenting quality was identified as a crucial factor influencing students’ adaptation, as supportive, emotionally responsive parenting can strengthen resilience and reduce the adverse effects of family disruption. In addition, social support from teachers, peers, schools, and communities serves as an important protective factor, enhancing students’ emotional stability and educational persistence. The review also reveals that educational outcomes among students from broken homes are multidimensional and influenced by interactions among psychological, social, and economic factors. This study contributes to educational literature by providing an integrative understanding of the relationships among family structure, parenting patterns, social support, and educational achievement. The study emphasizes the importance of inclusive educational environments, socio-emotional learning, and school-based counseling interventions to support vulnerable students. Therefore, collaborative efforts among families, schools, communities, and policymakers are essential to promote students’ emotional well-being and academic success despite family instability.